Effect of concurrent chemoradiation with cisplatin versus concurrent chemoradiation with carboplatin in locally advanced carcinoma cervix: A quasi-experimental study (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: The standard approach for locally advanced cervical cancer is concurrent chemoradiation with platinum agents, preferably cisplatin. This study was aimed at comparing the treatment response and toxicity of carboplatin-based versus cisplatin-based concurrent chemoradiation in locally advanced carcinoma of the cervix.Methods: This quasi-experimental study was conducted from September 2022 to August 2023 on 80 patients with locally advanced carcinoma cervix. Patients were divided evenly between the two arms (40 in each Arm). Arm A received weekly cisplatin 40 mg/m2, Arm B received weekly carboplatin with an area under the curve equal to 2 during external beam radiation. Then all the patients in both arms were treated by intracavity brachytherapy. Each patient was evaluated weekly during treatment and three months after the completion to assess treatment response and treatment related acute toxicities.Results: After three months of completion of treatment, the response was statistically similar between arms [Arm A, 35 (87.5%) versus Arm B, 37 (92.5%), P=0.71]. In terms of toxicity, while Arm B had significantly less anaemia (P=0.03), vomiting (P=0.05), and renal toxicity (P=0.03) than Arm A. Other toxicities such as leucopenia, thrombocytopenia, nausea, hyponatremia, radiation-induced dermatitis, cystitis, proctitis, and diarrhea were similar between arms.Conclusion: Concurrent chemoradiotherapy with carboplatin had a similar therapeutic response to concurrent chemoradiotherapy with cisplatin in locally advanced cervical cancer. Furthermore, the carboplatin arm had lesser toxicity than the cisplatin arm in terms of anaemia, vomiting, and renal toxicity.